Translational research in oral oncology (Sage Publications, 2016)
Translational Research in Oral Oncology is an international, interdisciplinary, peer reviewed, open access journal. It provides an open access forum for the dissemination of high quality basic and clinical oncology research concerning neoplasms in the head and neck (including lip, tongue, oral cavity, oropharynx, salivary glands, sinuses, nose, nasopharynx, larynx, skull base, thyroid, and craniofacial region, and the related hard and soft tissues and lymph nodes).
Keywords: Mouth : Cancer : Periodicals; Oncology : Periodicals; Head and Neck Neoplasms; Oncology; Mouth : Cancer; Oncology